(3cJGH aj GdUfGYIs - (3CMeO Hf YhV Hf eMeO HGaVd GdeZQHjs
(3ChdgG (B:s
(3GdMeO ddg GdPj CHOY ef YGde Gdchf eG ChLOg ef YLGFH eUfhYGJ eG OHQg ef SGda GdReGf hHYO gh Cfj ef YfahGf THGHj TZdJ HeWGdYI cJH GdeJbOejf ef GdYdeGA hGdMceGA GdChdjf eeG s
(3BNQgG (B:s
(3BNQ eG cJH ajg hGNJdGa CdhGfgG hYed GdeOGO hcPdc GdCMHGQ hZjQgG aj GdGJ GdSdGM hLdGFgG heKd UbGd GdSdGM ef GdSjha s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3djHjL (B(755) s
Keywords: (3eJaQbGJs